Evaluation of Temporal and Spatial Changes in Al-Sin Lake Water Quality Parameters - عسيكريه عزيز (Latakia University Journal -Engineering Sciences Series, 2025)
Al-Sin Lake, which supplies the cities of Lattakia and Tartous governorates with drinking water, is exposed to pollution from human activities in its basin, which causes a deterioration in its water quality. The research aims to evaluate Al-Sin Lake water quality and the need for the water treatment before using it for drinking. The aims were conducted through studying the temporal and spatial changes of several physicochemical and microbial parameters of water quality, which were measured three times monthly in 2021 from four different locations according to the program approved by the concerned staff to monitor and protect the lake. One-Way ANOVA was used to determine whether there is significantly spatial difference in water quality parameters among the four monitoring points. The research results showed significant spatial differences between the four monitoring points in some significant water quality parameters, including fecal coliforms counts in the water, water turbidity, and the concentrations of ammonia, nitrite, nitrate and phosphate in the water. They were also showed that the water characteristics in feeding springs area of Al-Sin Lake, where the Tartous drinking water intake is located, are better than those at the Lattakia drinking water intake, as the water from Tartus drinking water intake only needs to be sterilized before pumping it to Tartus, unlike the water from Lattakia drinking water intake which needs to be treated and sterilized. The results confirm the necessity of preventing the growth of floating plants and algae on the edges and bottom of the lake, to reduce the organic load in the lake, especially since the purification system in the Lattakia drinking water purification plant and the pumping system in Tartous drinking water pumping plant are not qualified to remove it from the water, as well as the sterilization process in both plants is currently performed using chlorine.